Functional analysis of the inhibitory neurotransmitter transporters GlyT1, GAT‐1, and GAT‐3 in astrocytes of the lateral superior olive. Issue 12 (7th August 2014) - Stephan, Jonathan; Friauf, Eckhard
<x xml:space="preserve">Abstract</x> Neurotransmitter clearance from the synaptic cleft is a major function of astrocytes and requires neurotransmitter transporters. In the rodent lateral superior olive (LSO), a conspicuous auditory brainstem center, both glycine and GABA mediate synaptic inhibition. However, the main inhibitory input from the medial nucleus of the trapezoid body (MNTB) appears to be glycinergic by postnatal day (P) 14, when circuit maturation is almost accomplished. Using whole‐cell patch‐clamp recordings at P3‐20, we analyzed glycine transporters (GlyT1) and GABA transporters (GAT‐1, GAT‐3) in mouse LSO astrocytes, emphasizing on their developmental regulation. Application of glycine or GABA induced a dose‐ and age‐dependent inward current and a respective depolarization. The GlyT1‐specific inhibitor sarcosine reduced the maximal glycine‐induced current (IGly (max)) by about 60%. The GAT‐1 and GAT‐3 antagonists NO711 and SNAP5114, respectively, reduced the maximal GABA‐induced current (IGABA (max)) by about 35%. Furthermore, [Cl−]o reduction decreased IGly (max) and IGABA (max) by about 85 to 95%, showing the Cl− dependence of GlyT and GAT. IGABA (max) was stronger than IGly (max), and the ratio increased developmentally from 1.6‐fold to 3.7‐fold. Together, our results demonstrate the functional presence of the three inhibitory neurotransmitter transporters GlyT1, GAT‐1, and GAT‐3 in LSO astrocytes. Furthermore, the uptake capability for GABA was higher than for glycine, pointing toward eminent GABAergic signaling in the LSO. GABA may originate from another source than the MNTB‐LSO synapses, namely from another projection or from reversal of astrocytic GATs. Thus, neuronal signaling in the LSO appears to be more versatile than previously thought. GLIA 2014;62:1992–2003